(untitled) (Research, Society and Development, 2022)
The main purpose of this article is to investigate which general aspects are related to education in (and for) diversity and how these issues relate to and converge with the postulations of an Integral Human Formation, in the context of Vocational and Technological Education (EPT). By demonstrating these convergences, we propose to answer the following question: Would the study of diversity be, in fact, a preponderant question for the process of human formation in its entirety? Therefore, a bibliographic analysis was carried out on the subject, focusing on the concepts and contextualization of diversity, identity and difference, highlighting how these conceptions are permeated by the existing power relations in society and influence its social constructions. As an argumentative direction, the article highlights some aspects related to gender, ethnic-racial and sexual diversities. At the end of the research, it was possible to recognize the real convergence between the critical historical study of diversity with the conceptions of Integral Human Formation, since diversity is in the scope of social relations where life is produced, and it is precisely the critical analysis of the totality of the social relations one of the commitments of the Integral Human Formation. Furthermore, by offering an in-depth study of the issues inherent to diversity, it is possible to understand the historical genesis of phenomena such as racism, machismo and homophobia and to envision alternatives for the construction of a more just and egalitarian society.